Pérégrinations et pérégrinismes dans le roman britannique du xixe siècle : Casuistique du détour par la langue étrangère - Jacqueline Fromonot (Cahiers Victoriens et Edouardiens)
This paper is a study of the role of peregrinism in Victorian novels, through examples taken from great classics, novels by Dickens, Thackeray, Eliot and Trollope. It will appear that the use of xenism in fiction is related to the quest of truth and truthfulness—in accordance with the Realist project. However, the stylistic analysis reveals that this figure of diversion also generates double-entendre and ambiguity.